Developing a Standardized Scale to Measure Teachers’ Perception and Attitude Towards Apprenticeship Embedded Degree Programme - Gorai, Jitendranath; Angadi, Gavisiddappa R. (Voices of Teachers and Teacher Educators, 2023)
In the framework of the Apprenticeship Embedded Degree Programme (AEDP), as envisioned in NEP-2020, this study aimed at developing a standardised Scale Towards an Apprenticeship Programme. Hence, the objective is to construct, develop and standardise the Teachers’ Perception and Attitude Scale Towards Apprenticeship Programme” (TPAS-TAP). The researchers used a five-point Likert scale in this study (Strongly Agree, Agree, Undecided, Disagree, and Strongly Disagree). 310 teachers from different high schools, colleges, and universities (assistant/associate/professors) working in India’s West Bengal’s “Rarh Region”.The data were analysed with the help of a quantitative research technique (through statistical software). The final TPAS-TAP version has 25 items in it after the item analysis. The scale is appropriate for the study, according to Cronbach’s Alpha, which was 0.856. The Factorial validity and the Split-half technique were revealed to be 0.84, indicating that the study was acceptable and reliable. The researcher employed the structural equation model and goodness of fit index (CMIN/DF= 2.981) to analyse and study the relationship between components. The RMSEA was 0.040; IBM SPSS (V-28) Amos software was used to analyse the Scale. This research can provide valuable insights for policymakers and researchers on shifting teachers’ perspectives and attitudes as stakeholders. Additionally, it can shed light on the various dimensions that can be utilised to effectively manage the new UGC degree program, which incorporates an apprenticeship, and comprehend the process of constructing and developing research scales